Compromised mammillary body connectivity and psychotic symptoms in mice with di- and mesencephalic ablation of ST8SIA2 - Küçükerden, Melike; Schuster, Ute E.; Röckle, Iris; Alvarez-Bolado, Gonzalo; Schwabe, Kerstin; Hildebrandt, Herbert (Translational Psychiatry, 2022)
Altered long-range connectivity is a common finding across neurodevelopmental psychiatric disorders, but causes and consequences are not well understood. Genetic variation in ST8SIA2 has been associated with schizophrenia, autism, and bipolar disorder, and St8sia2−/− mice show a number of related neurodevelopmental and behavioral phenotypes. In the present study, we use conditional knockout (cKO) to dissect neurodevelopmental defects and behavioral consequences of St8sia2 deficiency in cortical interneurons, their cortical environment, or in the di- and mesencephalon. Neither separate nor combined cortical and diencephalic ablation of St8sia2 caused the disturbed thalamus-cortex connectivity observed in St8sia2−/− mice. However, cortical ablation reproduced hypoplasia of corpus callosum and fornix and mice with di- and mesencephalic ablation displayed smaller mammillary bodies with a prominent loss of parvalbumin-positive projection neurons and size reductions of the mammillothalamic tract. In addition, the mammillotegmental tract and the mammillary peduncle, forming the reciprocal connections between mammillary bodies and Gudden’s tegmental nuclei, as well as the size of Gudden’s ventral tegmental nucleus were affected. Only mice with these mammillary deficits displayed enhanced MK-801-induced locomotor activity, exacerbated impairment of prepulse inhibition in response to apomorphine, and hypoanxiety in the elevated plus maze. We therefore propose that compromised mammillary body connectivity, independent from hippocampal input, leads to these psychotic-like responses of St8sia2-deficient mice.
Gesehen am 12.09.2022